Tindak Pidana Penganiayaan dalam Hukum Pidana Islam - Alfan Maulidin Ichwanto (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Crime is a problem that people experience from time to time. This shows that crime occurs and evolves in the environment of human life. One of the evils that continue to develop is a criminal act of persecution. This paper describes a criminal act of persecution in Islamic criminal law. This paper concludes with four conclusions. First, that the elements of jarimah of the forehead are: (1) causing pain or injury, (2) not with proper intent and purpose, and (3) accompanied by the intention of harming others. Second, that sanction of persecution is qisas or ta'zir. Thirdly, that if a criminal act of persecution is imposed a sanction of qisas on the limbs then it is required (1) not exaggerated, (2) the existence of similarity in name and location, and (3) the similarity between the two criminals and the victim in terms of health and perfection. Fourthly, that in addition to it can also be imposed sanctions diyah, the fine instead of qisas and penalties other than qisas.